2014
DOI: 10.1016/j.jml.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

How children explore the phonological network in child-directed speech: A survival analysis of children’s first word productions

Abstract: We explored how phonological network structure influences the age of words’ first appearance in children’s (14–50 months) speech, using a large, longitudinal corpus of spontaneous child-caregiver interactions. We represent the caregiver lexicon as a network in which each word is connected to all of its phonological neighbors, and consider both words’ local neighborhood density (degree), and also their embeddedness among interconnected neighborhoods (clustering coefficient and coreness). The larger-scale struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 111 publications
(238 reference statements)
3
55
0
1
Order By: Relevance
“…First, the growth models corroborate the findings of constraints on maximum degree in repertoire formation. Second, within the constraints of our models, word assembly ordered by word length is a likelier explanation of the data than random word addition, giving a quantitative basis to the hypothesis that language evolved from short to long words, similar to the language acquisition of children who tend to learn shorter words first [15,48,47,21]. Third, the analysis points towards a marked core-periphery structure of the English PN, suggesting that in the earlier stages of repertoire formation, preferentially such short words which are similar to (or can be derived from) multiple existing words have been assembled to the language, as already suggested in the psycholinguistic literature [31].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…First, the growth models corroborate the findings of constraints on maximum degree in repertoire formation. Second, within the constraints of our models, word assembly ordered by word length is a likelier explanation of the data than random word addition, giving a quantitative basis to the hypothesis that language evolved from short to long words, similar to the language acquisition of children who tend to learn shorter words first [15,48,47,21]. Third, the analysis points towards a marked core-periphery structure of the English PN, suggesting that in the earlier stages of repertoire formation, preferentially such short words which are similar to (or can be derived from) multiple existing words have been assembled to the language, as already suggested in the psycholinguistic literature [31].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When analyzing phonological properties of caregiver speech, it was found that children under 30 months were most likely to produce words with a high degree and low coreness (a measure of how deeply a node is embedded in a network) [53]. Larger scale architectural properties may also play a role in accessing the mental lexicon.…”
Section: Network Topology Influences Learning and Memorymentioning
confidence: 99%
“…Evidence is emerging that production‐based representations exist even before infants produce meaningful speech (Bruderer, Danielson, Kandhadai, & Werker, ; DePaolis, Vihman, & Keren‐Portnoy, ; DePaolis, Vihman, & Nakai, ; Majorano, Vihman, & DePaolis, ; Ngon & Peperkamp, ; Yeung & Werker, ). In addition to observing that there is a relationship between infants’ babbling repertories and their first words (Vihman, Macken, Miller, Simmons & Miller, ), children are more likely to add words to their productive vocabulary when the words are shorter in word length, have more phonological neighbours (i.e., words that sound similar to many other words), and are more frequent (Carlson, Sonderegger, & Bane, ; Coady & Aslin, ; Maekawa & Storkel, ; Ota & Green, ; Stoel‐Gammon, ; Storkel, , ). Some work has also indicated a relationship between children's speech production skills and their lexical acquisition.…”
Section: Introductionmentioning
confidence: 99%